Effect of steam thermal treatment on the drying process of Eucalyptus dunnii variables - Severo, Elias Taylor Durgante [UNESP]; Tomaselli, Ivan; Calonego, Fred Willians [UNESP]; Ferreira, André Luiz; Mendes, Lourival Marin (Universidade Federal de Lavras (UFLA), 2013)
The aim of this study was to evaluate the effect of steam treatment prior to drying on the initial moisture content, moisture gradient, and drying rate in Eucalyptus dunnii Maiden wood. Boards were steamed at 100ºC for 3 h after 1 h of heating-up. Part of these boards was dried in a drying electric oven at 50ºC, and part was dried at kiln. The results showed that the steaming prior to drying of wood: (1) significantly reduced by 9.2% the initial moisture content; (2) significantly increased by 6.2% the drying rate; (3) significantly decreased by 15.6 and 14.8% the moisture gradient between the outer layer and the center of boards and between the outer and intermediate layers of boards, respectively. Steamed boards when dried in an oven showed drying rate of 0.007065 whereas in kiln were 0.008200 and 0.034300 from green to 17 and 17 to 12% moisture content, respectively. It was demonstrated that the steaming prior to drying can be suitable for reduces the drying times of this kind of wood.

Objetivou-se, neste estudo, avaliar o efeito do tratamento de vapor preliminar à secagem sobre o teor de umidade inicial, gradiente de umidade e taxa de secagem da madeira de Eucalyptus dunnii Maiden. Tábuas foram vaporizadas à 100ºC após 1 hora de aquecimento inicial. Parte dessas tábuas foi seca em uma estufa elétrica à 50ºC, e outra parte foi seca em estufa de secagem convencional. Os resultados mostraram que a vaporização preliminar à secagem da madeira: (1) reduziu significativamente o teor de umidade inicial em 9.2%; (2) aumentou significativamente a taxa de secagem em 6.2%; (3) diminuiu significativamente o gradiente de umidade entre a camada externa e o centro das tábuas em 15.6%, e entre a camada intermediária e o centro das tábuas em 14.8%. As tábuas vaporizadas quando secas em estufa elétrica apresentaram taxa de secagem de 0.007065, enquanto que em estufa convencional foram 0.008200 e 0.034300 desde verde a 17% e de 17% a 12% de umidade, respectivamente. Ficou demonstrado que a vaporização preliminar à secagem pode ser responsável pela redução no tempo de secagem da madeira dessa espécie.
Efeito do tratamento térmico com vapor nas variáveis do processo de secagem de Eucalyptus dunnii
Keywords: Taxa de secagem; eucalyptus; gradiente de umidade; vaporização preliminar à secagem; Drying rate; eucalipto; moisture gradient; steaming prior to drying